2009
DOI: 10.1163/156856108x379100
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behaviour of Aluminum Bonded Joints as a Function of Wedge Test Performance

Abstract: An investigation of the factors affecting the wedge test performance of aluminum joints, prepared by bonding Al2024-T3 clad with FM300 epoxy adhesive, was conducted. It identified a number of factors whose influence was quantified in a regression model. The wedge test specimens were then machined into simple overlap fatigue specimens and cycled at a maximum stress of 20 MPa in shear and an R-ratio of 0.5. The results show that the log of the fatigue life is negatively correlated with the length of the crack pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Underhill et al [4] investigated the factors affecting the wedge test performance of aluminium (Al) adhesively bonded joints (Figure 4). They found that the specimens having the shortest crack length in the wedge test had the longest fatigue lives with the least amount of scatter.…”
Section: Effect Of Geometric Parametersmentioning
confidence: 99%
“…Underhill et al [4] investigated the factors affecting the wedge test performance of aluminium (Al) adhesively bonded joints (Figure 4). They found that the specimens having the shortest crack length in the wedge test had the longest fatigue lives with the least amount of scatter.…”
Section: Effect Of Geometric Parametersmentioning
confidence: 99%